Queering the Virgin: Evangelical World-Making and the Heterosexual Crisis - Jennifer Miller (European Journal of American Studies)
This interpretive essay reads US evangelical purity culture through queer theory demonstrating that the evangelical investment in virginity now produces the evangelical virgin as a politicized subaltern subject position. Aspects of purity culture including purity balls are theorized as undertaking an unexpectedly queer world making project.